Las nuevas tecnologías de la información y comunicación, y su influencia en el proceso de enseñanza aprendizaje, de los estudiantes de la facultad de ciencias de la salud – escuela de tecnología médica, modalidad semipresencial de la Universidad Nacional de Chimborazo (UNACH), periodo 2010-2011. Lineamientos alternativos - Moncayo Molina, Wilson Edwin (2014)
The present work was oriented to know The New Technologies of Information and Communication, and its Influence on the Teaching-Learning Process in students from the School of Medical Technology UNACH, Semipresential Modality, period 2010-2011; alternative guidelines, in order to achieve benefits to overcome problems detected. The inductive, deductive and descriptive methods guided the process; as the survey technique applied to teachers, students and administrators in the study area was used. From the analysis and interpretation of results and the corresponding discussion it is concluded that the influence of NTIC, using teachers and assessment of students in the teaching-learning can improve the quality of the study in a Semipresential Modality, it suggests using this system to form critical, innovative and research professionals. Finally alternative guidelines are established the problems investigated in search of contribute to solving the problems detected.